Influence of drinking water quality on the formation of corrosion scales in lead-bearing drinking water distribution systems. Issue 12 (15th October 2021) - Guo, Daoping; Herrera, Jose E.
Abstract: Lead in drinking water occurs in drinking water distribution systems (DWDS) where lead pipes are used as service lines. Using data gathered from 4 different Canadian cities, we link drinking water quality to composition of corrosion scales obtained on exhumed lead pipes servicing those municipalities. The data presented encompasses a 10-year span and a detailed layer profile analysis of the solids present in lead bearing service lines; where different layers within the corrosion scale formed inside lead pipes are identified and thoroughly characterized. The results obtained clearly show that the corrosion layers in direct contact with drinking water are rich in lead oxides phases and aluminosilicates. In contrast, lead carbonates are the main phases present on corrosion scales in direct contact with the metallic lead pipe. This heterogeneity on phase distribution is correlated to the radial distance from the corrosion scales to the water/solid interphase and water quality servicing those municipalities. Statistical analysis suggests that dissolved Al, Mn, Cu, Ni, and As accumulate on the corrosion scales with preferential accumulation of specific elements heavily dependent on distinct municipality water quality.